Polylactic acid (PLA) biocomposites reinforced with coir fibres: Evaluation of mechanical performance and multifunctional properties - Dong, Yu; Ghataura, Arvinder; Takagi, H.; Haroosh, Hazim Jasim Mohammed; Nakagaito, A.; Lau, K. (Pergamon, 2014)
The effects of fibre content (5-30 wt%) and fibre treatment on surface morphology, tensile, flexural, thermal and biodegradable properties of polylactic acid (PLA)/coir fibre biocomposites were evaluated via scanning electron microscopy (SEM), mechanical testing, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and soil burial method. Similar decreasing trends were found for tensile and flexural strengths with higher strength values obtained for PLA/treated coir fibre biocomposites. 20 wt% treated coir fibres were determined to achieve optimum tensile and flexural strengths of biocomposites. Regardless of fibre treatment, the thermal stability of biocomposites is worsened with increasing the fibre content. The decreased cold crystallisation temperatures of biocomposites further confirms the effective nucleating agent role of coir fibres. The biocomposites undergo much faster degradation than PLA, with the maximum weight loss of 34.9% in treated fibre biocomposites relative to 18% in PLA after 18-day burial, arising from the hydrophilic nature of coir fibres.